Placental erythropoietin expression is upregulated in growth-restricted fetuses with abnormal umbilical artery Doppler findings: a case-control study of monochorionic twins - Yao-Lung Chang; An-Shine Chao; Hsiu-Huei Peng; Shuenn-Dyh Chang; Kuan-Ju Chen; Po-Jen Cheng; Tzu-Hao Wang (BMC, 2018)
Abstract Background We previously reported that fetal plasma erythropoietin (EPO) concentrations are significantly increased in growth-restricted fetuses with abnormal umbilical artery (UA) Doppler. During hypoxia in an ovine model, the primary site of fetal EPO synthesis was switched from the kidneys to the placenta. Therefore, we designed this study to evaluate human placental EPO gene expression and the correlation to fetal serum EPO concentration in growth-restricted fetuses in a monochorionic (MC) twin model. Methods In MC twin pairs, selective intrauterine growth restriction (sIUGR) was defined as the presence of (i) birth weight discordance of > 20% and (ii) a smaller twin with a birth weight less than the 10th percentile. Fetal UA and middle cerebral artery (MCA) Doppler were checked within 1 week before delivery. An abnormal UA Doppler was defined as persistently absent or reverse end-diastolic flow. Cerebroplacental ratio (CPR) was defined as MCA-pulsatility index (PI)/UA-PI. Fetal plasma EPO concentrations were measured in cord blood, and EPO gene expression was assayed in each twin's placental territory. The intertwin plasma EPO ratio was calculated as the cord plasma EPO level of the smaller (or sIUGR) twin divided by the EPO concentration of the larger (or appropriate-for-gestational-age (AGA)) twin, and the intertwin placental EPO gene expression ratio was calculated similarly. Results Twenty-six MC twins were analyzed, including normal twins (Group 1, n = 9), twins with sIUGR without UA Doppler abnormalities (Group 2, n = 9), and twins with sIUGR and UA Doppler abnormalities (Group 3, n = 8). The CPRs of smaller (sIUGR) fetuses were significantly decreased in Group 3 MC twins (p < 0.001), but not significantly different between Group 1 and Group 2. The highest fetal plasma EPO ratio and placental EPO gene expression ratio were identified in Group 3 MC twins (p < 0.001). The placental EPO gene expression ratios were significantly correlated with the fetal plasma EPO ratios (Pearson's correlation test, p = 0.004). Conclusion This study provides evidence of increased placental EPO expression in MC twin fetuses with sIUGR and abnormal UA Doppler. Future studies are needed to confirm the similar role of placental EPO in severe IUGR singletons.